PENGARUH PENERAPAN GAYA MENGAJAR RESIPROKAL TERHADAP GERAK DASAR PASSING BAWAH DALAM PERMAINAN BOLA VOLI PADA SISWA SMA NEGERI 1 TONDANO - Eduardo Semuel Lenzun; Djajaty Lolowang; Nolfie Piri (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The problem in this research is whether the provision of a reciprocal teaching style has an effect on basic motor skills in passing down in volleyball in students at SMA Negeri 1 Tondano. This study aims to test the average basic movement ability in lower passing in volleyball. The research method used is an experimental research method. The population in this study was all students of SMA Negeri 1 Tondano class XI, totaling 100 students. The sample in this study was taken from 30% of the total population, namely, 30 class XI students at SMA Negeri 1 Tondano. The research instrument used was a test of basic lower passing movement abilities according to the Ministry of National Education. The results of statistical analysis using the t test statistic, obtained a tcount of 6.35. Based on the t distribution table at ∝ 0.05 with degrees of freedom n1 + n2 – 2 =15 +15 – 2 = 28, we get a t table of 2,048. So tcount is greater than ttable, namely tcount = 6.35 > ttable = 2.048. Based on the test criteria, if tcount is greater than ttable (tcount>ttable) then Ho is rejected, which means HA is accepted. Based on the results of hypothesis testing using the t test statistic, the results of this research can be concluded that there is an influence of the reciprocal teaching style on the ability of basic lower passing movements in volleyball among students at SMA Negeri 1 Tondano.